Meningkatkan Kualitas Pemasaran Produk Kopi dan Kualitas Pendidikan di Dusun Durjo, Desa Karangpring, Jember - Rojabi, Ahmad Ridho; Gofar, Arrifa Aulliyatul; Septian, Windi Ika; Efendi, Mohammad Makhzumi Irvan; Savina, Rina; Karimah, Iqla Nur (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Community empowerment programs should be implemented to raise awareness among local communities about the potential that exists in the area. The purpose of this study is to provide an overview of educational programs for elementary school students by immersing them in three educational institutions in Durjo Karangpring village, as well as an overview of service programs by educating coffee youth on how to increase sales of products that are already available in the area. This study employs the ABCD (asset-based community development) method, with data collected through interviews, observations, and documentation. These findings demonstrate an increase in education through both formal and informal learning activities. This activity can be implemented on a continuous basis by the surrounding community, allowing students to learn informally as well as formally at school. The socialization program for coffee product marketing strategies is extremely beneficial for young people since it helps them understand how to improve coffee product marketing and compete with other coffee products.